Diversification of processed yellow pumpkin products (Cucurbita Moschata) in efforts to develop household culinary businesses - Nasution, Siti Khadijah Hidayati; Fatoni, R.B.Moh Ibrahim (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2019)
The development of SMEs in the culinary in Medan has increased every year. Market opportunities provide SMEs to grow. Diversification in food processing can be done by adding pumpkin (Cucurbita Moschata) into food dough food so that it becomes a different product from those in the market. YAAHFTICS is a SMEs which is engaged in culinary, especially birthday cake, pizza, roll cake and others. Mitra has been established since 2015. Partners rely on marketing through social media Instagram. In running the business cycle, partners experience several major problems. Starting in terms of business financial management, product diversification to the problem of quantity production. The aim of the Community Service Program activities is that Partners can increase their production capacity so that they can increase their income, able to produce diversified processed products from pumpkins, and able to determine product prices with optimal profit. The method of activity used is the delivery of production equipment, the practice of using production equipment to increase production capacity, the practice of making diversified processed pumpkin products and monitoring the production and sales processes. The results of the oven and mixer grant in this service activity can increase the partner’s production capacity product. After counseling the importance of product diversification and the practise of diversification of pumpkin processed pumpkin products, the partner have been able to diversity their processed pumpkin products. And the partner have been able to determine product prices with optimal profit after the partner has been given training in determining the cost of goods sold.